Diamine derivative of a ruthenium(II)-polypyridyl complex for chemodosimetric detection of nitrite ion in aqueous solution - Ghosh, Amrita; Das, Priyadip; Saha, Sukdeb; Banerjee, Tanmay; Bhatt, Harshad B.; Das, Amitava (Inorganica Chimica Acta, 2011)
Nitrite is quite an abundant anion in the environment. It, however, becomes toxic to human life, as well as aquatic animals when present above the permissible concentration level. We have reported here a Ru(II)-polypyridyl-based complex (1) for chemodosimetric detection of nitrite ion in aqueous solution. Formation of the new triazole based complex, generated by reaction of 1 and N2O3, is ascertained by comparing its properties with a presynthesised triazole complex.